Kajian Perbedaan Interior Ruang antara Vihara dan Klenteng di Tarakan - Irawan, Jenny (Intra, 2015)
The building of each religion has a different style of building form and every religion has a different. After doing some research, questionnaire and interview also studied the literature about places of worship of religious Buddhist and Khong Hu Chu, author finds there is an interesting difference in some house of worship, one of which is the place of the religion of Buddha and the Khong Hu Chu. So the issue is interesting to review. To review them, the author uses qualitative deskriptif research methods, where this method is to differentiate between an object and another object. So it can be seen that can be seen from a few things. When seen in terms of building and the roof material used. When seenin detail on the interior, both Temples and Monasteries, both set is still influenced by Chinese architecture.